Nevinost bez zastite - Makavejev, Dusan (Yugoslavia, 1968)
In 1942 a professional strong man named Dragoljub Aleksic directed and starred in a trite little melodrama titled Innocence Unprotected--the first Serbian talkie. Over 20 years later, Dusan Makavejev retrieved the film from the Archives, tinted many of the sequences by hand, and interviewed Aleksic and his co-workers in present day Yugoslavia 1968. The resulting cinematic collage is a funny and daring (in both content and form) mix of a wide variety of film footage--including documentary, narrative, agitprop, and various other bits and pieces of found footage. Serbian with English subtitles.
Keywords: Fiction films